Conceptualizing Longitudinal Mixed Methods Designs: A Methodological Review of Health Sciences Research. (October 2015) - Plano Clark, Vicki L.; Anderson, Nancy; Wertz, Jessica A.; Zhou, Yuchun; Schumacher, Karen; Miaskowski, Christine
Longitudinal research is well suited for investigating phenomena that change over time. With the growing acceptance of mixed methods, researchers are combining qualitative and quantitative approaches within longitudinal research. However, little attention has been paid to how researchers integrate longitudinal mixed methods databases. The purpose of this methodological review was to describe how researchers combine mixed methods and longitudinal approaches in practice and delineate dimensions and issues inherent within these complex designs. We examined published empirical studies from the health sciences that self-identified as longitudinal and mixed methods. Our results identify major dimensions, variations, and issues for designing longitudinal mixed methods research and suggest recommendations for researchers interested in using this complex approach.